2005
DOI: 10.1007/s00417-005-0028-1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of sodium hyaluronate eyedrops in the treatment of dry eye

Abstract: Sodium hyaluronate of 0.1% and 0.3% reduces symptoms of ocular irritation and lengthens NIBUT in subjects with moderate dry eye more effectively than saline, in terms of peak effect and duration of action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
106
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(123 citation statements)
references
References 9 publications
10
106
0
7
Order By: Relevance
“…It is likely Clinitas Soothe was preferred by more participants than Hyabak due to the higher concentration of sodium hyaluronate contained in Clinitas Soothe (0.4%) when compared to Hyabak (0.15%), as found previously [2].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…It is likely Clinitas Soothe was preferred by more participants than Hyabak due to the higher concentration of sodium hyaluronate contained in Clinitas Soothe (0.4%) when compared to Hyabak (0.15%), as found previously [2].…”
Section: Discussionsupporting
confidence: 69%
“…Sodium hyaluronate increases tear film stability by increasing tear film viscosity between blinks [2]. Clinical trials of sodium hyaluronate dry eye treatment have reported an increase in ocular comfort [1][2][3][4]15], a reduction in NaFl corneal staining [3], a reduction in Rose Bengal staining [28], an increase in NITBUT [2,4], an increase in Schirmer's score [29] and an improvement in impression cytology grading [16]. Sodium hyaluronate is a naturally occurring glycosaminoglycan of the extracellular matrix and a ligand for the hyaluronate receptor CD44 [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have proved the safety and the efficacy of native HA solutions as artificial tears [222,[224][225][226]. More recently, also novel derivatives of hyaluronan with improved mechanical and biological properties are being investigated to formulate eye drops with enhanced ocular residence times.…”
Section: Ophthalmologic Surgery and Ophthalmologymentioning
confidence: 99%
“…21,22 HA is used as a tear substitute for dry eyes to increase tear film stability and reduce subjective symptoms, such as ocular irritation and burning. [23][24][25] Thus, HA is a remarkable biopolymer that appears to have an impressive array of biological functions.…”
Section: Introductionmentioning
confidence: 99%